Nonsuch Palace The Material Culture of a Noble Restoration Household - Biddle, Martin (Historic England, 2005)
Nonsuch in Surrey was Henry VIII's last and most fantastic palace. Begun in 1538, at the start of the 30th year of Henry's reign, the palace was intended as a triumphal celebration of the power and the grandeur of Henry VIII and the Tudor dynasty. The site was chosen for its fine countryside and hunting potential. The palace was ornately decorated with intricate Renaissance designs in carved and gilded slate and plasterwork, with two great octagonal towers, five storeys high at either end. The finds fall into two categories: architectural and domestic. This volume, the second in the series, publishes the domestic finds, including a large amount of complete or reconstructible glass, ceramics (such as tin-glazed wares, stoneware and earthenware), coins and tokens, clay pipes, pewter vessels, objects of iron, bone, ivory and leather, and a wooden pocket sundial.